The Parenting Working Mothers to Stimulate Children's Intelligence - Raras Ayu Prawinda; Dessy Farantika (SINDA: Comprehensive Journal of Islamic Social Studies, 2021)
The development of children's intrapersonal intelligence is closely related to the parenting applied by parents at home. Parents' knowledge and understanding of child care using appropriate parenting patterns. Authoritative parenting is a parenting style that encourages individuals to be independent but still maintain limits and control over the actions taken. Applying authoritative parenting to children is that mothers expect their children to grow and develop as well as possible, able to control emotions naturally, have the ability to manage themselves even though working mothers have limited time in accompanying and caring for children at home like mothers who do not work. This study seeks to reveal the authoritative parenting carried out by working mothers to stimulate the intrapersonal intelligence of early childhood through in-depth observations of the conditions and situations of authoritative parenting in the daily lives of mothers and children at home. Conditions in the field that run as they are in accordance with the reality in the field are very useful for researchers to obtain data. The approach used in this research is a qualitative descriptive approach. The type of research used in this qualitative research is a single case study.